Endosulfan, pentachlorobenzene and short-chain chlorinated paraffins in background soils from Western Europe. (January 2015) - Halse, Anne Karine; Schlabach, Martin; Schuster, Jasmin K.; Jones, Kevin C.; Steinnes, Eiliv; Breivik, Knut
Abstract: Soils are major reservoirs for many persistent organic pollutants (POPs). In this study, "newly" regulated POPs i.e. Σendosulfans (α-endosulfan, β-endosulfan, endosulfan sulfate), pentachlorobenzene (PeCB), and short-chain chlorinated paraffins (SCCPs) were determined in background samples from woodland (WL) and grassland (GL) surface soil, collected along an existing latitudinal UK–Norway transect. Statistical analysis, complemented with plots showing the predicted equilibrium distribution and mobility potential, was then explored to discuss factors controlling their spatial distribution. SCCPs were detected with the highest average concentrations (35 ± 100 ng/g soil organic matter (SOM)), followed by Σendosulfans (3 ± 3 ng/g SOM) and PeCB (1 ± 1 ng/g SOM). PeCB and Σendosulfans share many similarities in their distribution in these background soils as well as with several legacy POPs. A steep decline in concentrations of SCCPs with increasing latitude indicates that their occurrence is dictated by proximity to source regions, while concentrations of Σendosulfans peaked in regions experiencing elevated precipitation rates. Graphical abstract: Highlights: "Newly" regulated POPs are reported in background soils. ΣEndosulfans and PeCB were each significantly correlated with legacy POPs. Soil organic matter (SOM) and black carbon (BC) are key variables. Combining statistics and chemical space maps facilitate a mechanistic understanding. Abstract : Processes affecting the occurrence and latitudinal distribution of some "newly" regulated POPs in background soils.